Cell sizing in chronic lymphoproliferative disorders: an aid to differential diagnosis. Issue 10 (October 1992) - Alexander, H D; Markey, G M; Nolan, R L; Morris, T C
Abstract : AIMS: To determine if leucocyte volume distribution analysis (LVDA), obtained using a Coulter Counter Model S Plus IV, can be used to aid differentiation of chronic lymphoproliferative disorder (CLPD) subtypes. METHODS: Mean lymphocyte volume and lymphocyte distribution width were measured on each patient (n = 90) using a hard copy of an amplified LVDA histogram. The mean lymphocyte volume was taken as the mean of the values on either side of the peak at half maximum height. The lymphocyte distribution width was taken as the range of cell values between the two values used to calibrate the mean lymphocyte volume. A template showing typical histograms from commonly occurring CLPD was also produced on an acetate sheet. This was used to examine the histogram from each new patient to evaluate its usefulness as an alternative to the calculation of mean lymphocyte volume and lymphocyte distribution width. RESULTS: Mean lymphocyte volume and lymphocyte distribution width were significantly higher in B cell lymphocytic leukaemia of mixed cell type (B CLL/PL), B cell non-Hodgkin's lymphoma with peripheral blood spill, hairy cell leukaemia and T cell prolymphocytic leukaemia than in B cell chronic lymphocytic leukaemia (B CLL). The mean lymphocyte volume, but not the lymphocyte distribution width, was also significantly higher in T cell chronic lymphocytic leukaemia than in B CLL. The template gave an immediate preliminary indication of possible subtype(s) of disorder and could be used as an alternative to measurement of mean lymphocyte volume and lymphocyte distribution width. CONCLUSIONS: Electronic haematology analysers producing an LVDA provide a useful, cost effective cell sizing analysis which can aid the differentiation of subtypes of CLPD.